2022
DOI: 10.1016/j.amsu.2021.103128
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognostic factors of atrial fibrillation at a tertiary center of Pakistan – From a South-Asian perspective – A cross-sectional study

Abstract: Background There is lack of large data from South-Asian region on atrial fibrillation and it is imperative that clinical presentation, prognostic factors, management pursued, and outcomes are known for this part of the world. Once collective evidence for the region is known, region-specific guidelines can be laid forward. Objectives To evaluate clinical characteristics and prognostic factors of atrial fibrillation at a tertiary care center of Pakistan. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The commonest indication for implant was AV Block 60.5 % (98) out of which majority of study participants had complete AV block while others were implanted for 2:1 AV block. AV block was followed by left ventricular systolic dysfunction 25.3% (41), sinus node dysfunction 16% (26), chronic bifascicular and trifascicular block 4.3% (7). Out of the studied population, 58% (n=94) participants were pacemaker dependent and 35.8% (n=58) had the rate response feature turned on.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The commonest indication for implant was AV Block 60.5 % (98) out of which majority of study participants had complete AV block while others were implanted for 2:1 AV block. AV block was followed by left ventricular systolic dysfunction 25.3% (41), sinus node dysfunction 16% (26), chronic bifascicular and trifascicular block 4.3% (7). Out of the studied population, 58% (n=94) participants were pacemaker dependent and 35.8% (n=58) had the rate response feature turned on.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 Prior literatures also reports a higher risk of AF with certain comorbid conditions namely hypertension, diabetes mellitus, and hyperlipidemia. 6,7 However, the primary limitation of these earlier studies has been the preexistence of AF in the study population, and we know that prior AF is a dominant harbinger of more AF. 8 It is evident from prior studies that the occurrence of AF may result in cerebrovascular accident (CVA).…”
Section: Introductionmentioning
confidence: 97%
“… 40 , 41 A study from Pakistan showed a prevalence of 6.5% among acute medical admissions, pointing toward the underestimated burden in African countries. 42 A subgroup analysis from the Randomized Evaluation of Long-Term Anticoagulation Therapy (RE-LY) Registry showed regional disparities in the prevalence of AF, anticoagulation strategies, and risk factors. 43 The investigation concluded there was a lower prevalence of AF in LMICs compared to HICs.…”
Section: Epidemiology Of Arrhythmias In Lmicsmentioning
confidence: 99%
“…Pakistan is the fifth largest country in the world by population, with 242 million people 35 . Unfortunately, there are no national data available, but coronary heart disease and associated risk factors and infectious disease are likely the largest health issues in Pakistan 36,37 . Arrhythmias are likely the third major cardiovascular problem behind coronary artery disease and heart failure.…”
Section: Individual Country Reportsmentioning
confidence: 99%
“…35 Unfortunately, there are no national data available, but coronary heart disease and associated risk factors and infectious disease are likely the largest health issues in Pakistan. 36,37 Arrhythmias are likely the third major cardiovascular problem behind coronary artery disease and heart failure. SVT, followed by AF (mainly because of rheumatic heart disease), and bradycardia are the three most important arrhythmia issues in Pakistan.…”
Section: Pakistanmentioning
confidence: 99%